Regulation of the Hippocampal Network by VGLUT3-Positive CCK- GABAergic Basket Cells - Fasano, Caroline; Rocchetti, Jill; Pietrajtis, Katarzyna; Zander, Johannes-Friedrich; Manseau, Frédéric; Sakae, Diana Y.; Marcus-Sells, Maya; Ramet, Lauriane; Morel, Lydie J.; Carrel, Damien; Dumas, Sylvie; Bolte, Susanne; et al. (Frontiers in Cellular Neuroscience, 2017)
Hippocampal interneurons release the inhibitory transmitter GABA to regulate excitation, rhythm generation and synaptic plasticity. A subpopulation of GABAergic basket cells co-expresses the GABA/glycine vesicular transporters (VIAAT) and the atypical type III vesicular glutamate transporter (VGLUT3); therefore, these cells have the ability to signal with both GABA and glutamate. GABAergic transmission by basket cells has been extensively characterized but nothing is known about the functional implications of VGLUT3-dependent glutamate released by these cells. Here, using VGLUT3-null mice we observed that the loss of VGLUT3 results in a metaplastic shift in synaptic plasticity at Shaeffer’s collaterals - CA1 synapses and an altered theta oscillation. These changes were paralleled by the loss of a VGLUT3-dependent inhibition of GABAergic current in CA1 pyramidal layer. Therefore presynaptic type III metabotropic could be activated by glutamate released from VGLUT3-positive interneurons. This putative presynaptic heterologous feedback mechanism inhibits local GABAergic tone regulates the hippocampal neuronal network.